Unity of bowel-lung axis and the role of beneficial microbiota in anti-infectious protection - T.E. Taranushenko (LCC «Medicine-Inform», 2021)
T.E. Taranushenko Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation NIH Human Microbiome Project determined particular attention of the worldwide medical community to the study of the human microbiome and the assessment of the impact of symbiont microorganisms in the development of various (not only gastrointestinal) disorders. Potential interactions between the bowel and lungs (bowel-lung axis) via microbiota that allow for the possible involvement of microorganisms in the development of respiratory diseases are actively debated. This paper reviews studies on the pattern of interactions between bowel and lungs in infectious diseases associated with mucosal inflammation. The association between gut microbiota and the protective barrier of the respiratory tract based on known mechanisms and novel data derived from recent studies on SARS-CoV-2 is discussed. The relevance of beneficial bacteria (symbionts) in local and systemic immune responses, their disease-modifying and, eventually, therapeutic strategy-modifying properties, the ability to be  a resource of preventive medicine and an orchestrating tool for infections are addressed. Practitioners' difficulties with probiotics in preventive and treatment schedules for various conditions are highlighted. Finally, the use of probiotics in children with respiratory infections and COVID-19 is uncovered. Keywords: microbiota, microbiome, probiotics, children, mucosal immunity, Bifidobacterium. For citation: Taranushenko T.E. Unity of bowel-lung axis and the role of beneficial microbiota in anti-infectious protection. Russian Journal of Woman and Child Health. 2021;4(4):355-361 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-355-361.